The use of dorsoradial forearm flap for the treatment of dorsal hand defect - Karakol, Perçin (J Surg Case Rep, 2020)
Generally dorsal hand defects are often closed with a flap. Dorsoradial forearm artery flap has generally been used in thumb defects; however, it can also be used in the reconstruction of dorsal hand defects thanks to its wide rotation arc and appropriate pedicle length. In this case report, we presented the outcome of a case where the dorsoradial forearm flap was applied to treat the dorsal hand defect. A 27-year-old patient was admitted to emergency room with trauma on hand. Fixation of metacarpal bone fractures was performed. The dorsoradial forearm flap was elevated and inserted in order to close an opening exposing bones and tendons in the dorsum of hand. There was no complication with flap viability in the postoperative period. Patient’s joint range of motion and vital functions were acceptable. Dorsoradial forearm flap, which is generally used in thumb reconstruction, can also be used in dorsal hand defects.